RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND MOTIVATION TO WORK WITH THE COMMITMENT OF THE ORGANIZATION AT RSUD BOGOR - Ratno . (The Management Journal of Binaniaga, 2017)
The purpose of this study was to determine whether there is a relationship between organizational culture and work motivation and organizational commitment partially and simultaneously. The population for this study were permanent employees Bogor City Hospital with a population of as many as 533 employees are part of the medical and non medis.Sampel taken as many as 224 people by using techniques Slovin formula. Mechanical questionnaires using proportional random sampling technique. The research instrument was a questionnaire. Collected data is processed using correlation analysis technique with SPSS (Statistical Package for Social Science). The results showed that: First of organizational culture has a positive relationship with organizational commitment to the value of 0.782, this relationship into the category of a strong relationship. While the influence of organizational culture on organizational commitment of 61.1%. Both work motivation has a positive relationship with organizational commitment to the value of 0.766, this relationship into the category of a strong relationship. While the influence of work motivation on organizational commitment amounted to 58.7%. Third Culture organization (X1) and motivation (X2) simultaneously have a positive relationship with organizational commitment (Y) of = 0.841, this relationship indicates a very strong relationship between the variables of organizational culture and work motivation simultaneously with variable organizational commitment. The influence of organizational culture (X1) and motivation (X2) simultaneously with organizational commitment (Y) by 70.8% against organizational commitment (Y).Keywords: Organizational Culture, Work Motivation and Organizational Commitment